Nopyl acetate production by esterification of acetic acid and nopol over heterogeneous catalysts (2019)
ABSTRACT: Nopyl acetate is an artificial fragrance compound with a fruity odor of fresh wood which is not present in nature and it is used in the preparation of soaps, detergents, creams, lotions and perfumes. It is conventionally prepared by the carbonyl-ene reaction of β-pinene and paraformaldehyde with subsequent acetylation of the intermediary nopol with acetic anhydride. As the esterification reaction in the absence of a catalyst is slow and reversible and water is one of the by-products, a hydrothermal stable material is required as catalyst. There are few reports about the synthesis of nopyl acetate. It was reported that the reaction at 200 °C of β-pinene with paraformaldehyde in the presence of acetic anhydride produces nopyl acetate with a 60 % yield after 5 h. For nopol esterification with carboxylic chloride acids in triethanol amine and dichloromethane solution, nopyl acetate yields of 79 % (5 to 25 °C) were achieved. Nopyl acetate may be synthesized from acetic anhydride and sodium acetate, with 84 % yield (3 h, 90 ° C) after its separation and purification. It is possible to obtain yields of 98 % (150 °C, 1 h) by reacting nopol with acetic anhydride in the presence of toluene or chlorobenzene, removing the carboxylic acid by-product by azeotropic distillation. The synthesis of nopyl acetate with acetic anhydride in the presence of triethylamine and dimethylaminopyridine (DMAP) in dichloromethane as solvent at room temperature, with quantitative yields, has been reported. Using ammonium and cerium nitrate catalyst, (NH4)Ce(NO3)6 in CH2Cl2 as solvent at 40-50 °C, nopyl acetate is obtained with a 92 % yield. Costa et al. reported in 2016 the use of tungstophosphoric heteropoly acid H3PW12O40 (HPW) and its acidic Cs salt Cs2.5H0.5PW12O40 (CsPW) for the liquid phase acetylation of nopol. The reaction occurs at room temperature with low catalyst loadings and can be performed solvent-free with stoichiometric amounts of acetic anhydride providing excellent yields (100%). Recently, environmental and economic considerations have promoted innovation processes towards the use of cleaner technologies. Therefore, there is a great challenge of using heterogeneous catalysts that can perform under mild reaction conditions, for example at low temperatures and pressures, while avoiding the use of harmful substances such as amines and chlorinated compounds. Systems reported for the esterification of other alcohols could be considered as possible alternatives for the esterification of nopol. Tin modified mesoporous materials (MCM-41 and SBA-15) could be attractive alternatives with voluminous organic molecules like nopol. Ionic exchange resins like Amberlyst – 15, with functional group –SO3H, have been used in the esterification of primary alcohols with acetic acid. Sn-SBA-15 is an acid catalyst, with a mesoporous support that would avoid mobility restriction of reactants and products. Additionally, Sn-MCM-41 has been found to be a suitable mesoporous material for nopol production. The use of Sn supported on SiO2 is an economical option, as well as Amberlyst-15. p-toluenesulfonic acid (PTSA) has the potential to be used as a substitute for conventional acidic catalytic materials. It is characterized by the mildness of the reaction conditions, inexpensive chemical and the excellent functional group tolerance, allowing the formation of the corresponding esters in good to excellent yields. The objective of this research is to determine the most adequate catalyst and reaction conditions for nopyl acetate synthesis in order to achieve highest reaction rate. Sn-MCM-41, Sn-SBA-15 and Sn-SiO2 heterogeneous catalysts were synthesized by incipient wetness impregnation using SnCl2 • 2H2O as precursor at room temperature. Physicochemical properties of the materials were determined by surface area BET (Brunauer, Emmett and Teller), SEM (Scanning Electron Microscopy), AAS (Atomic Absorption Spectroscopy) of Sn, NH3-TPD (Ammonia Temperature Programmed Desorption), FTIR (Fourier-transform Infrared Spectroscopy), UV-vis (Ultraviolet–visible spectroscopy), Raman spectroscopy, XRD (X-ray Diffraction), and TGA (Thermal Gravimetric Analysis). Characterization of MCM-41 and SBA-15 materials verified that synthesized catalysts have ordered hexagonal mesostructures. The XRD patterns of Sn-SBA-15 and Sn-MCM- 41 were very similar to those of the supports. SEM micrographs indicated that SBA-15 and Sn-SBA-15 showed the characteristic morphology of SBA-15, represented in domains in the form of loops that are added to a microstructure similar to wheat. The N2 adsorption and desorption isotherms of the materials were type IV, which is typical of mesoporous materials. The BET areas of SBA-15 and Sn-SBA-15 were 531 and 471 m2/g respectively. Surface area of MCM-41 decreased from 596 to 576 m2/g by incorporating tin. SiO2 and Sn-SiO2 surface areas were 434 and 364 m2/g, respectively. TPD analysis established the presence of strong (1.42 mmol NH3/g cat), medium (0.08 mmol NH3/g cat) and weak acid sites (0.24 mmol NH3/g cat) in the materials. For kinetic tests with Amberlyst-15 and Sn-SBA-15, an average particle size of 58-76.5 μm and stirring speeds between 500 and 1000 rpm were used for guarantying the absence of diffusion effects for kinetic tests. Acetic acid and acetic anhydride were used as esterifying agents. In presence of n-hexane, nopyl acetate selectivity over Sn-SBA-15 was 15.2 % and Sn-MCM-41 displayed best ester selectivity (17.8 %) in toluene at a 2:1 acetic acid: alcohol molar ratio. Amberlyst-15 reaches 100 % nopol conversion in presence of toluene at acetic acid: alcohol ratios of 1:2, 1:1 and 2:1. Synthesis of nopyl acetate was satisfactory using homogeneous catalyst p-toluenesulfonic acid (p-TSA), achieving a selectivity of 45.6 % and a nopol conversion of 99.7 % compared to Amberlyst-15 with 9 % ester selectivity and 57.6 % alcohol conversion. Using acetic anhydride, Sn-SiO2 reaches 75 % nopol conversion at 60 min making it an active and selective material for nopyl acetate synthesis. Amberlyst-15 exhibited best and more stable catalytic activity and with Sn-SiO2 catalyst, best nopyl acetate selectivity was attained. Catalyst reusability was performed separating the material by decantation; washing it three times with acetone under continuous stirring and drying it in an oven at 80 °C overnight. This procedure was carried out before every reuse. The reusability tests were carried out with Amberlyst-15 that was the material that showed the highest nopol conversion, and it was found that the material loses catalytic activity in the fourth cycle, although leaching of the active species does not occur. The structural properties of Sn-SBA-15, the high catalytic performance and the economic viability of Sn-SiO2 make these materials potential to replace homogeneous acid catalysts in the nopol esterification reaction. Best nopyl acetate selectivity (100 %) is obtained over Sn-SiO2, achieving a 75 % nopol conversion at 60 min, with a 3:1 acetic anhydride: alcohol molar ratio in presence of toluene, 80 °C and 750 rpm. Using Amberlyst-15, nopyl acetate selectivity reaches 8.2 % and 65.8 % nopol conversion at reaction times 90-120 min, 6.1 mg/mL catalyst loading, 80 °C, 750 rpm, nopol/ toluene solution 0.25 M and a 2:1 acetic acid: alcohol molar ratio.